Push-out bond strength and marginal adaptation of apical plugs with bioactive endodontic cements in simulated immature teeth - Maria Aparecida Barbosa de Sá; Eduardo Nunes; Alberto Nogueira da Gama Antunes; Manoel Brito Júnior; Martinho Campolina Rebello Horta; Rodrigo Rodrigues Amaral; Stephen Cohen; Frank Ferreira Silveira (Restorative Dentistry & Endodontics, 2021)
ObjectivesThis study evaluates the bond strength and marginal adaptation of mineral trioxide aggregate (MTA) Repair HP and Biodentine used as apical plugs; MTA was used as reference material for comparison.Materials and MethodsA total of 30 single-rooted teeth with standardized, artificially created open apices were randomly divided into 3 groups (n = 10 per group), according to the material used to form 6-mm-thick apical plugs: group 1 (MTA Repair HP); group 2 (Biodentine); and group 3 (white MTA). Subsequently, the specimens were transversely sectioned to obtain 2 (cervical and apical) 2.5-mm-thick slices per root. Epoxy resin replicas were observed under a scanning electron microscope to measure the gap size at the material/dentin interface (the largest and smaller gaps were recorded for each replica). The bond strength of the investigated materials to dentin was determined using the push-out test. The variable bond strengths and gap sizes were evaluated independently at the apical and cervical root dentin slices. Data were analyzed using descriptive and analytic statistics.ResultsThe comparison between the groups regarding the variables' bond strengths and gap sizes showed no statistical difference (p > 0.05) except for a single difference in the smallest gap at the cervical root dentin slice, which was higher in group 3 than in group 1 (p < 0.05).ConclusionsThe bond strength and marginal adaptation to root canal walls of MTA HP and Biodentine cement were comparable to white MTA.